Prediksi Sebaran Air Limbah Batubara di Badan Air Permukaan (Anak Sungai X) Dengan Memperhatikan Musim Barat Dan Timur Menggunakan Software MIKE 21 - Rizka Novembrianto; Rizal Fachrudin (Prosiding ESEC, 2023)
Increasing the daerah of the coal pit and disposal, planned additional outlet points in the project daerah (port activities). Wastewater in the form of rainwater runoff in the stockpile, to the washing of materials containing heavy metals, will enter the Settling Pond before being discharged into the X tributary. A numerical approach using MIKE 21 software which was applied taking into the western and eastern seasons. It was found that the highest temperature concentration reached 26°C, at outfall-1.7 km in the west and east seasons. The highest pH concentration in the east season reached 6.139, at outfall-1.7 km. The highest TSS concentration reached 15.0 ppm, at distance of 0.4-0.6 km in the west and east seasons. The highest Fe concentration reached 0.952 ppm, at outfall-0.25 km in the west and east seasons. Also, the highest Mn concentration reached 0.448 ppm, at distance 0.25 km in the west and east seasons. Based on PP no. 22/2021 Appendix VI Class 2 National Water Quality Standards, the temperature parameter Dev 3°C, the pH parameter 6-9, the TSS parameter 50 ppm, and the Fe and Mn parameters are not required, so only the pH parameter does not meet the quality standard.